Depressive Realism: Wiser or Quieter? - Blanco, Fernando; Matute, Helena; Vadillo, Miguel A. (Psychological Record)
Depressive realism consists of the lower personal control over uncontrollable events perceived by depressed as compared to nondepressed individuals. In this article, we propose that the realism of depressed individuals is caused not by an increased accuracy in perception, but by their more comprehensive exposure to the actual environmental contingencies, which in turn is due to their more passive pattern of responding. To test this hypothesis, dysphoric and nondysphoric participants were exposed to an uncontrollable task and both their probability of responding and their judgment of control were assessed. As was expected, higher levels of depression correlated negatively with probability of responding and with the illusion of control. Implications for a therapy of depression are discussed. Reprinted by permission of the publisher.